Are Patient-Reported Outcome Scores a Reasonable Substitute for Clinical Follow-up After Surgically Managed Acromioclavicular Joint Injuries?. Issue 5 (13th May 2022) - Dey Hazra, Rony-Orijit; Blach, Robert Maximillian; Ziert, Yvonne; Ellwein, Alexander; Warnhoff, Mara; Hanhoff, Marek; Lill, Helmut; Jensen, Gunnar
Background: Various clinical outcome scores have been described to evaluate postoperative shoulder function after operatively treated acromioclavicular joint (ACJ) instability. Clinical outcome scores can be divided between patient-reported outcome measures (PROMs) and examiner-dependent outcome measures (EDOMs) after a clinical examination by a physician. The correlation between PROMs and EDOMs, and thus their interchangeability with regard to operatively treated ACJ instability, has not yet been evaluated. Purpose: To investigate whether PROMs are a reasonable substitute for EDOMs. Correlations between global shoulder (GS) and ACJ-specific outcome measures were also investigated. Study Design: Cohort study (diagnosis); Level of evidence, 3. Methods: Included in this study were 131 consecutive patients with operatively treated ACJ instability between 2011 and 2017. Postoperative shoulder function was measured using PROMs, including the Subjective Shoulder Value (SSV), Subjective Shoulder Test, and Nottingham Clavicle Score (NCS), and EDOMs, including the Constant-Murley score (CMS), Taft score, ACJ instability (ACJI) score, and SICK Scapula Score (SSS). Associations between PROM and EDOM scores were calculated using the Pearson and Spearman correlation coefficients for linear and nonlinear variables, respectively, and were interpreted using the Cohen classification. The scores were further stratified into GS versus ACJ-specific measures. Results: A strong correlation was observed between several PROMs and EDOMs (CMS vs SSV [ r = 0.59; P = .02] and CMS vs NCS [ r = 0.79; P ≤ .001]) and between several GS and ACJ-specific scores (CMS vs NCS; CMS vs ACJI [ rs = 0.69; P < .001]; and CMS vs SSS [ r = –0.68; P < .001]). Conclusion: Based on the results of this study, PROMs such as the SSV (a GS measure) and the NCS (an ACJ-specific measure) can substitute for EDOMs. Clinical Relevance: PROMs that can be substituted for EDOMs can enable the conduct of clinical studies in circumstances in which in-person clinical follow-up of the patient by a physician is not possible.